CHILDREN BENEFIT INFORMATION SYSTEM INFORMATION SYSTEM IN THE SEMARANG SETARA NGO - Pouty Delima, Revael Miralia; Agus Diartono, Dwi (Information Technology and Telematics, 2018)
Abstract - The equivalent foundation is a child protection organization that focuses on the fulfillment of child rights. As partners from the government and international NGOs, the foundation is equivalent to having hundreds of families and children accompanied. The purpose of this study was to design an archival system application for beneficiaries of assisted children shaded by the Setara NGO in Semarang. The method used to design the system is to use the waterfall method. While the software used (software) used is Mysql as a database. The results of research on NGOs Equivalent can be concluded that with the construction of archival information system of beneficiaries of Setara Semarang can minimize archive storage and facilitate the search for child data.